STUDI EKSPERIMENTAL KUAT LENTUR BAJA PROFIL I KOMPAK SIMETRIS GANDA BERDASARKAN RSNI 03-1729-201X - Redaksi Tim Jurnal (FORUM MEKANIKA, 2017)
The danger of buckling and instability structures easily occurs on the steel beam structure, it will make the structure fails before it reaches the cross section ultimate capacity.In that case the strength of a beam is not only determined by cross-section ultimate capacity. The instability of the structure causes lateral torsional buckling eventhough there is no torque on the beam. There is one way to support the stability of the beam; by installing lateral support on its side. This research is intended to obtain information about flexural strength by comparing the theoretical results based on SNI 03-1729-2002 and (Indonesian National Standard Draft) RSNI 03-1729.1- 201x with the results of experimental testing and finite element analysis results (using the ABAQUS program). The flexural specimens which are studied are in the long-span with a length of 3.3 meters span test. The loading uses three-point load system. The results of the test show information that flexural strength for the long-span specimen from experimental test results has the smallest difference of 33.18% of the theoretical result. As for analysis with FEM also hasthe same difference of 33.18% with the experimental results. Failure that occurs for long-span specimen is due to lateral torsional buckling failures.